Configuring and troubleshooting Windows XP Professional - Barber, Brian; Grasdal, Martin (Rockland, Mass. : Syngress Pub., 2001)
In October of 2001, Microsoft will begin its most expensive market launch ever for Windows XP With the promise of a market launch twice the size of the one for Windows 95, Microsoft will undoubtedly drive enormous demand for its Windows XP desktop operating system. Many corporate and small business users have waited to upgrade from Windows 9x, and they now see WinXP as the stable, second generation of Windows 2000 Professional. Syngress's Windows 2000 books were the first out on the market when W2K was released and quickly became bestsellers. Configuring and Troubleshooting Windows XP Professional aims to be the the first book available on this new product. Designed to compete directly with books such as Mastering Windows 2000 Professional, by Mark Minasi, Configuring and Troubleshooting Windows XP Professional is comprehensive guide for system administrators and network engineers responsible for deploying Windows XP Professional across the network. The first Windows XP Professional book on the market Not 'for Dummies' - this is an essential reference guide for certified Windows 2000 administrators and engineers Edited by Tom Shinder, the best-selling author of Configuring ISA Server 2000 Unrivalled web support at www.solutions@syngress.com.
Next Generation Windows -- Installing Windows XP Professional -- Exploring the Windows XP User Interface -- Managing Windows XP Professional -- Working with System Tools -- Windows XP Networking -- Configuring Internet Technologies -- Adding New Hardware and Software -- Using the Communication Tools -- Using the Control Panel -- Understanding Windows XP Security -- Using IntelliMirror Technologies -- Working with Printers -- Troubleshooting Windows XP -- Best Practice Disaster Recovery and Prevention.
Includes index.
Keywords: Microsoft Windows (Computer file).; Operating systems (Computers).; Electronic books